COVID-19 vaccination, perceptions about the vaccine and willingness to take the vaccine among unvaccinated individuals at two Ugandan border points of entry - Joseph K. B. Matovu; Rebecca Nuwematsiko; Christine Aanyu; Lilian Tabwenda; Tom Okade; David Musoke; Esther Buregyeya (BMC Public Health)
Abstract Background A recent systematic review shows high COVID-19 vaccine effectiveness in fully-vaccinated people in Africa. However, vaccine uptake has varied across populations. We assessed the uptake, perceptions of and willingness to take the COVID-19 vaccine among unvaccinated individuals at two Ugandan border points of entry. Methods This was a cross-sectional quantitative study conducted at Malaba and Mutukula points of entry into Uganda between February and March 2023. We targeted people living in, working at, or transiting through the two points of entry, including truck drivers, point-of-entry customs officers and female sex workers, market vendors, among others. Data were collected on socio-demographic characteristics, vaccine uptake, perceptions and willingness to take the vaccine among unvaccinated individuals. We computed descriptive statistics and determined the factors associated with uptake of and willingness to take the vaccine using a modified Poisson regression model. Data analysis was conducted using STATA statistical package (version 14.0). Results Of the 854 respondents, 50% (n = 427) were from Mutukula. Overall, 80.3% (n = 686) of the respondents reported that they had received at least one vaccine dose; no booster doses were reported. Respondents perceived that the vaccine was efficacious against COVID-19. COVID-19 vaccine uptake was associated with age-group 35–44 years [adjusted Prevalence Ratio [aPR] (95%CI) = 1.13 (1.01, 1.27)] or 45 + years [aPR (95%CI) = 1.19 (1.07, 1.33)]; being a truck driver [aPR (95%CI) = 1.16 (1.04, 1.29)] or health worker [aPR (95%CI) = 1.18 (1.05, 1.32)]; and the belief that the COVID-19 vaccine is protective against COVID-19 [aPR (95%CI) = 1.32 (1.10, 1.58)]. Nearly 60% of unvaccinated respondents (n = 99) were willing to take the COVID-19 vaccine. Willingness to take the vaccine was associated with the belief that one can contract the coronavirus if not vaccinated [aPR (95%CI) = 3.67 (1.90, 7.10)] or the community was at risk of COVID-19 [aPR (95%CI) = 1.86 (1.33, 2.62)]. Conclusion COVID-19 vaccine uptake was high in this setting while nearly six out of every ten unvaccinated individuals were willing to take the vaccine. Our findings lend credence for ongoing vaccination efforts at points of entry to contain the importation of new COVID-19 variants into the country.